Identification of BgP, a Cutinase-Like Polyesterase From a Deep-Sea Sponge-Derived Actinobacterium - Carr, Clodagh M.; de Oliveira, Bruno Francesco Rodrigues; Jackson, Stephen A.; Laport, Marinella Silva; Clarke, David J.; Dobson, Alan D. W. (Frontiers in Microbiology, 2022)
Many marine bacteria produce extracellular enzymes that degrade complex molecules to facilitate their growth in environmental conditions that are often harsh and low in nutrients. Marine bacteria, including those inhabiting sea sponges, have previously been reported to be a promising source of polyesterase enzymes, which have received recent attention due to their potential ability to degrade polyethylene terephthalate (PET) plastic. During the screening of 51 marine bacterial isolates for hydrolytic activities targeting ester and polyester substrates, a Brachybacterium ginsengisoli B129SM11 isolate from the deep-sea sponge Pheronema sp. was identified as a good polyesterase producer. Sequence analysis of genomic DNA from strain B129SM11, coupled with a genome “mining” strategy allowed the identification of potential polyesterases, using a custom database of enzymes; that had previously been reported to hydrolyze PET and other synthetic polyesters. This resulted in the identification of a putative PET hydrolase gene, encoding a polyesterase-type enzyme which we named BgP; that shared high overall similarity with three well-characterized PET hydrolases- LCC, TfCut2, and Cut190, all of which are key enzymes involved in the biological recycling of PET. In silico protein analyses and homology protein modelling offered structural and functional insights into BgP, and a detailed comparison with Cut190 revealed highly conserved features with implications for both catalysis and substrate binding. Polyesterase activity was confirmed using an agar-based polycaprolactone (PCL) clearing assay, following heterologous expression of BgP in Escherichia coli. This is the first report of a polyesterase being identified from a deep-sea sponge bacterium such as Brachybacterium ginsengisoli and provides further insights into marine derived polyesterases, an important family of enzymes for PET plastic hydrolysis. Microorganisms living in association with sponges are likely to have increased exposure to plastics and microplastics given the wide scale contamination of our marine ecosystems with these plastics, and thus they may represent a worthwhile source of enzymes for use in new plastic waste management systems. This study adds to the growing knowledge of microbial polyesterases and in particular endorses further exploration of marine host-associated microorganisms as a potential valuable source of this family of enzymes for PET plastic hydrolysis.